1001 Vrouwen in perspectief. Traditie en verandering van het biografische woordenboek in Nederland en elders - Bosch, Mineke (BMGN - Low Countries Historical Review, 2014)
1001 Women in Perspective: Tradition and Change in the Biographical Dictionaries of the Netherlands and ElsewhereIn this article Mineke Bosch discusses the book 1001 Women from Dutch History, published in February 2013 and edited by Els Kloek, against the background of the tradition and recent change of national dictionaries of biography. Since the nineteenth century this historical genre has played a central role in processes of canonisation within national history. The gender order that is written into these biographical reference works is now considered out of date. Since the 1970s, therefore, corrections have been made. In the United States, for instance, a special dictionary of women’s biography appeared, the Notable American Women, as a ‘supplement’ to the standard Dictionary of American Biography. The British Dictionary of National Biography decided to add to and rewrite all the existing lemma’sbetween 1994 and 2004, to reappear as the Oxford Dictionary of National Biography. This work represents a paradigm change as the basic question of inclusion is no longer ‘who survived history?’, but ‘who deserves a lemma in our contemporary vision of history?’ In this historical perspective Bosch answers such questions as what is the relation between 1001 Women and the Dutch Biographical Dictionary of the Netherlands. Was it the aim of the book to confront gendered processes of canonisation? Can the work be seen as ‘a contribution to’ (herstory) or a ‘rewriting of’ history? In dit artikel bespreekt Mineke Bosch het in februari 2013 onder redactie van Els Kloek uitgekomen 1001 Vrouwen uit de Nederlandse geschiedenis in het perspectief van traditie en verandering van het biografisch woordenboek. Sinds de negentiende eeuw speelt dit genre van het historische standaardwerk een centrale rol in canoniseringsprocessen binnen de nationale geschiedschrijving. De genderorde die in deze biografische woordenboeken werd vervat, blijkt echter niet meer vandeze tijd. Sinds de jaren zeventig van de vorige eeuw zijn daar dan ook correcties op uitgevoerd. In Amerika verscheen bijvoorbeeld als aanvulling op de Dictionary of American Biography een biografisch woordenboek van vrouwen, de Notable American Women. De Britse Dictionary of National Biography daarentegen, besloot tot een aanvulling én algehele herschrijving van alle lemma’s, om opnieuw te verschijnen als Oxford Dictionary of National Biography. In dit werk is sprake vaneen paradigmawisseling omdat de basisvraag voor opname niet meer is wie in het verleden kwam bovendrijven, maar wie volgens hedendaagse normen van geschiedschrijving een lemma verdient. Tegen deze historische achtergrond beantwoordt Bosch vragen over hoe de relatie is tussen 1001 Vrouwen en het Biografisch Woordenboek van Nederland. Was het de bedoeling om bestaande gegenderde canoniseringsprocessen tegen te gaan? Is het werk te beschouwen als ‘herstory’ of als een ‘herschrijving’ van de geschiedenis?